HISTOLOGICAL AND HISTOCHEMICAL CHANGES OF THE LUNGS AFTER EXPERIMENTAL THERMAL TRAUMA - Небесна, З.М.; Єрошенко, Г.А. (World of Medicine and Biology, 2015)
In the experiment on mature white male rats performed histological and histochemical research of the lungs was studied after thermal trauma. It was established that the degree of structural and histochemical changes in components of organ depends on the term of experiment. Changes in the early stages after burn injury (1-7 days) are characterized by adaptative-compensatory and initial destructive changes. In the later stages of the experiment (14-21 days) significant vascular disorders were found, destructive-degenerative changes of bronchi and respiratory portion, lungs.
Keywords: lungs; histological and histochemical changes; thermal trauma